The role of IL-1 and Type I IFN in CNS function - MURRAY, CAROL (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
Cytokines including interleukins (ILs) and interferons (IFNs) are induced in response to tissue injury, infection or inflammation. Peripheral cytokines signal to the healthy Central Nervous System (CNS) to produce physiological, behavioural, affective, and cognitive changes collectively known as sickness behaviour. Sickness behaviour is an adaptive response that is beneficial to the organism, but when these inflammatory insults are superimposed upon neurodegeneration, they have deleterious effects such as delirium, an acute cognitive disorder prevalent in elderly and patients with dementia that has significant economic, medical and societal impacts. There is debate as to whether IL-1 is necessary or detrimental in learning and memory. The role this cytokine plays during systemic inflammation effects on the degenerating brain remains to be investigated in detail. Similarly though type I IFN’s are produced in the periphery during viral infection and in the brain during aging. Research into its effects on brain function is in its infancy. This thesis aimed to investigate the role of these cytokines on brain function in 3 scenarios, basal, induced and in the vulnerable brain. The effects of these cytokines were first examined at basal levels by using IL-1R1-/- mice and IFNAR1-/- mice to examine the behavioural and cognitive function after deletion of these key receptors. IL-1R1-/-mice and IFNAR1-/- mice displayed intact hippocampal-dependent memory. The IL-1R1-/- mice had a reduction in anxiety as seen with increased time spent in the open arms of the EPM, while IFNAR1-/- mice displayed similar levels of anxiety to WT controls. WT controls and knockout mice were then challenged systemically with LPS or Poly I:C to examine the effects of induction of these cytokines in cognition and behaviour. There were dissociable effects of LPS on two hippocampal- dependent memory tasks; working memory was intact while consolidation of memory was impaired in the CFC. IL-1RA failed to protect against LPS-induced memory consolidation deficits. To examine the effect of IL-1 during neurodegeneration, mice were inoculated with NBH or ME7 disease. ME7 mice were vulnerable to the LPS-induced deficits in working memory and both dexamethasone and IL-1RA systemically applied protected against the LPS-induced deficit in the T-maze, independently of CNS cytokine expression. LPS induced hypoglycaemia, and glucose administration to ME7 mice after LPS could ameliorate the LPS-induced deficits in the T-maze. When glycolysis and IL-1 synthesis were inhibited with 2-DG, this lead to decreased activity and increased sickness behaviour and glucose administration once again ameliorated these effects, indicating that systemic inflammation deficits are partially mediated by hypoglycaemia. The viral mimetic poly I:C triggered robust sickness behaviour and this was significantly diminished in IFNAR1-/-mice. Moreover STAT1 signalling and poly I:C-induced IL-6 were significantly diminished in IFNAR1-/- mice and supplementation with IL-6 reconstituted key aspects of the sickness behaviour response. Despite these suppressive impacts of IFN-I signalling on activity and sickness, IFNAR deletion during aging actually left mice more vulnerable to cognitive decline and decreased expression of microglial transcripts associated with neuronal maintenance. Together, these data indicate basal IL-1 and IFN-I in the normal brain have no influence on cognitive function but may influence anxiety. In the induced state, IL-1 certainly contributes to acute cognitive dysfunction in the vulnerable brain, and IFN-I contribute to the sickness behaviour response to acute viral mimetics. However, the absence of IFN-I as the brain ages may contribute to age-related cognitive decline. These finding have significant implication for age-related cognitive function and the understanding of the contribution of neuroinflammation to those processes. Considerable further work is required to validate these findings in clinical populations.
APPROVED
Keywords: Neuroinflammation, Behaviour, Delirium, Interleukin-1, Type one interferons